Security of present s-box - Taha, Imad; Salim, Sufyan (2012)
Resource efficient cryptographic primitives become fundamental for realizing both security and efficiency in embedded systems like RFID (Radio-Frequency IDentification) tags and sensor nodes. Among those primitives, lightweight block cipher plays a major role to secure RFID’s tag. One of the common lightweight block ciphers is PRESENT. In this paper, we attended both conditions of PRESENT substitution box S-box and those conditions of 4-bit S-box. They were studied and analyzed thoroughly in relation with linear and differential cryptanalysis. The results show that there is conflict in one of the conditions of PRESENT S-box.